A STUDY OF STUDENTS’ PROBLEMS AND SOLUTIONS IN LEARNING SPEAKING AT CLASS VIII BAHASA OF MTS PERGURUAN MU’ALLIMAT JOMBANG - Luluk Masruroh Azizah (Program Studi Pendidikan Bahasa Inggris, 2024)
Nowadays Indonesia lives in a world that is nearly using English in many aspects of life. With English we can easily interact with foreign, get job easily, and many more. In contrast, speaking English is the problem for the students. The present study aims at investigating some English-speaking problems encountered by the students at class 8 Bahasa of MTs Perguruan Muallimat Cukir Jombang and offering some solutions for English speaking problems itself. This study used a descriptive qualitative approach and the data were taken from semi-structured interviews, observation and Questionnaire. Students in class VIII Bahasa of MTs Perguruan Mu’allimat Jombang were chosen as the respondent of this research. There are 29 students who have been requested to complete a questionnaire and have been chosen as interviewers to express their opinions about the problems and challenges they encounter while they were learning speaking.The results of the analysis reveal that the problems encountered by the students in at class 8 Bahasa of MTs Perguruan Muallimat Cukir Jombang in speaking English cover the lack of motivation to speak English outside the class and English input in everyday life, lack of pronunciation, lack of vocabulary enrichment and lack of confidence. There have been some solutions offered to overcome students’ problem in speaking English. Firstly, a well-designed speaking curriculum is essential. Second, educators should create curricula for English-speaking students that use social media and technology and encourage them to learn about and experience different cultures. In order to give students additional opportunities to speak English both within and outside of the classroom, lecturers should thirdly support the English-speaking curriculum in collaboration with the English-speaking community. The study also provides presents suggestions for future research